Effect of return on asset and return on equity on stock price - Mottoh, Rommy J. R.; Supriyanto, Supriyanto (Institute of Computer Science (IOCS), 2024)
The purpose of this study was to determine the effect of Return on assets and return on equity on the share price of pharmaceutical subsector companies listed on the Indonesia Stock Exchange from 2020 to 2023. The sampling used in this study was purposive sampling method. The study population consisted of 12 pharmaceutical companies listed on the Indonesia Stock Exchange for the period 2020-2023 or 4 years and the number of samples in this study amounted to 10 companies. The indicator used to calculate the stock price is the stock price at the closing price. This type of research is quantitative research and the type of data used is secondary data in the form of financial reports which can be accessed at http: //www.idx.co.id. The results showed that ROA and ROE did not have a significant effect on stock prices, this was also evident from the t test, and the significance results of the return on assets and return on equity variables were smaller than the degree, namely 0.938> 0.05 for the ROA variable and 0.390> 0.05 for the ROE variable. The results of the f test research also show that return on assets and return on equity do not simultaneously affect stock prices because the significance value is greater than the degree of error, namely 0.079> 0.05.